Investigating the Feasibility and Impact of Perinatal Depression Screening and Treatment in Rural Nsambe, Malawi - Waste Kayira; Mark Chalamanda; Kingsley Kanzoole; Kondwani Mpinga; Moses Banda Aron; Ksakred Kelly; Sarah Singer; Enoch Ndarama; Stephanie Smith; Giuseppe Raviola; Basimenye Nhlema; Emilia Connolly; et al. (Intervention Journal of Mental Health and Psychosocial Support in Conflict Affected Areas)
Perinatal depression contributes significantly to morbidity and mortality of women and children in low- and middle-income countries. However, due to low resources and little evidence on the impact of screening and treatment, few interventions are offered. Our study aims to assess the feasibility and impact of depression symptoms with screening and treatment of women in rural Malawi. Screening for depression was conducted using the Patient Health Questionnaire 2 (PHQ-2) and PHQ-9. Women identified to have moderate and severe depression were treated through a group counselling intervention—WHO Group Problem Management Plus (group PM+). With integration of PHQ-2 into prenatal and antenatal clinic registration, 90.2% of women were screened with PHQ-2 and 12.8% of women screened positive for depression. Seventy-one women were treated with group PM+ over the study period with decreased depressive symptoms after course completion (mean PHQ-9 = 12.3 at enrollment and 2.3 after course [p < .05]) and at 6-month follow-up (mean PHQ-9 = 1.0 [p < .05]). Our findings suggest that it is feasible to screen and treat women with perinatal depression in rural Malawi and that group counselling through PM+ can lead to improvement of symptoms.